ADVERSE EVENT FOLLOWING PENTAVALENT IMMUNIZATION IN 6, 10 AND 14 WEEK. - Dr. Rubina Rafique; Muhammad Ali Shah; Nabeel Ahmad Khan; Saleha Tabassum; Shilpa Dahara; Zainab Abdul Razzak (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction Despite the limited data on adverse events following immunization (AEFIs), these events are thought to contribute to vaccine hesitancy. This study aims to thoroughly examine the practices surrounding the reporting and management of AEFIs, providing insights into their potential impact on public trust in vaccines. Method This prospective mixed-methods study included 457 in-person interviews with caregivers, 8 key informant interviews, and 7 focus group discussions. Caregivers were recruited at or before their child’s 6-week clinic visit and were then evaluated for the presence of AEFIs during subsequent appointments at 10 and 14 weeks, as well as through a follow-up call two weeks after the 14-week visit. Result Out of 209 children, 91 (43.5%) received scheduled vaccinations, with follow-up rates of 8.6% at 6 weeks, 41.6% at 10 weeks, and 8.1% at 14 weeks, while 41.6% completed all follow-ups. Common symptoms included pain, fever, and redness, affecting 25.4% of children, with 68.4% requiring medication and most recovering within 5 to 10 days. Notably, 98.6% of the reported cases were duplicates, leaving only 1.4% as primary cases. Conclusion The study’s findings reaffirm the safety and effectiveness of vaccines, demonstrating that while mild to moderate adverse events such as pain, fever, and redness were common, they were generally manageable and led to full recovery within a short period. The low incidence of severe adverse events underscores the importance of ongoing surveillance and transparent communication with caregivers to maintain public trust in vaccination programs. Overall, the benefits of vaccination significantly outweigh the risks, supporting its continued use as a vital public health measure.